Managing Contention for Shared Resources on Multicore Processors. - FEDOROVA, ALEXANDRA; BLAGODUROV, SERGEY; ZHURAVLEV, SERGEY (Communications of the ACM, 2010)
The article discusses managing shared resources on multicore processors. Topics covered include modeling contention for shared resources, incorporating contention models in a scheduler, assessing modeling techniques, and a prototype scheduler built by the authors that handles contention for resources based on miss rates of online threads. For this prototype and another aimed at scheduling workload applications, the authors present and discuss results. Their work shows that miss rates are an effective means of predicting contention.